2013
DOI: 10.1186/1756-0500-6-357
|View full text |Cite
|
Sign up to set email alerts
|

Do MCI patients with vitamin B12 deficiency have distinctive cognitive deficits?

Abstract: BackgroundVitamin B12 deficiency is common in older people, and may be responsible for reversible dementia. Low serum vitamin B12 levels were also observed in patients with Mild Cognitive Impairment (MCI). It is not known whether patients with vitamin B12 deficiency have a distinctive profile of cognitive impairment different from the episodic memory deficit usually observed in MCI.ResultsFrom a cohort of 310 patients with MCI followed in a memory clinic in Lisbon, only 10 cases with vitamin B12 deficiency wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
4
0
3
Order By: Relevance
“…On the other hand, the prospective study conducted by Clarke et al [30] found that there was no association between cognitive decline (assessed with MMSE scores) and lower vitamin B12 levels. Previous studies have postulated that possessing the APOE 4 allele in combination with other factors, such as level of education or B vitamin deficiencies, might increase the risk of dementia [43,44]. APOE is an aggravating factor of the association between homocysteine and dementia [45].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the prospective study conducted by Clarke et al [30] found that there was no association between cognitive decline (assessed with MMSE scores) and lower vitamin B12 levels. Previous studies have postulated that possessing the APOE 4 allele in combination with other factors, such as level of education or B vitamin deficiencies, might increase the risk of dementia [43,44]. APOE is an aggravating factor of the association between homocysteine and dementia [45].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a deficiency of this vitamin can be associated with a progressive atrophy of the brain and consequent cognitive decline 10 . Another study showed that in patients with MCI, low levels of this vitamin have not been associated with cognitive deficits, but its deficiency could precipitate the onset of symptoms 40 . Moore et al 41 concluded, after review of 43 studies on the subject, that vitamin B 12 deficiency may precede cognitive decline, but there is insufficient evidence to determine if this condition causes cognitive decline and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of patients with vitamin B12 deficiency in our clinic had B12 levels of 203-270 pg/mL, and most of them had no obvious complaints. Patients with vitamin B12 levels below 203 pg/mL were considered as having vitamin B12 deficiency 14 . Values below 135.4 pg/mL represented a serious deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The patient complaints included forgetfulness, loss of balance, numbness, and tingling and burning in hands and feet. Patients with serum B12 levels less than 200 pg/mL were considered as having vitamin B12 deficiency; patients with serum levels equal or higher than 200 pg/mL were considered normal 14 .…”
Section: Methodsmentioning
confidence: 99%